Impact of genotypic mixture on soybean (Glycine max) pest population - MEENA, LOKESH KUMAR; RAJESH, VANGALA; PATEL, RAM MANOHAR; SHARMA, AMAR NATH (The Indian Journal of Agricultural Sciences, 2024)
An experiment was conducted during rainy (kharif) seasons of 2018 and 2019 at the ICAR-Indian Institute of Soybean Research, Indore, and Madhya Pradesh to study the impact of genotypic mixture on soybean [Glycine max (L.) Merr.] pest population. A total of 16 soybean genotypes and 4 genotypic mixtures were evaluated for relative efficacy in management of insect-pests of soybean. Among the 20 treatments, the plots with genotypic mixtures had lowest population of Spodoptera exigua Hubner and at par with each other. In case of Spodoptera litura Fabricius, tussock moth, blue beetle and grey weevil management, a mixture of the genotypes JS-9560, JS-20-34, MAUS-47 and MACS-1460 was found most effective treatment. The plots with the genotypic mixtures of NRC-37, JS-9752, RSC-1046 and RKS-113 supported the least population of semiloopers. However, lowest population of leaf miner and girdle beetle was recorded in plots of JS-20-34 while the least population of stem fly was recorded in RSC-1046. The differences observed due to the genotypic combinations may be used for developing inset-pest management programmes in soybean.